Assessment of awareness of radiation protection and knowledge of radiation dose among 5th year medical students and radiology residents at Maharaj Nakorn Chiang Mai Hospital, Thailand - N, Inmutto; A, Sripusanapan; K, Jariyawattana; D, Natee; T, Pichcha; E, Tirisara (Biomedical Sciences and Clinical Medicine, 2020)
Objectives Our study aimed to assess the awareness of radiation protection and knowledge of radiation dose of 5th year medical students and radiology residents. Methods Forty-seven 5th year medical students and 18 radiology residents participated in this survey during July 10-17, 2019. Participation was voluntary and the identity of the respondents was kept anonymous. The participants were asked to complete the questionnaire via Google forms within a period of 15 minutes. Results The survey found that 48.9% of 5th year medical students and 61.1% of radiology residents felt they had sufficient knowledge of ionizing radiation protection. Counting one point for a correct answers and zero points for a wrong answer, the overall mean score of the 5th year medical students was 6.2 out of a possible 16 with a standard deviation of 2.2. The overall mean score of the radiology residents was 7.9 out of 16 with a standard deviation of 2.1. Only 14.9% of the medical students and 38.9% of the radiology residents knew about stochastic radiation damage. However, 57.4% of the medical students and 88.9% of the radiology residents did know about the “as low as reasonably achievable” (ALARA) concept. Fifty percent of the medical students did not know that MRI and ultrasound do not produce ionizing radiation. Conclusion There is evidence of inadequate awareness of radiation protection and knowledge of radiation doses among both 5th year medical students and radiology residents at Maharaj Nakorn Chiang Mai Hospital, Thailand. To improve this situation, adding theoretical and practical modules to the standard curricula should be considered.